Feasibility of Vacuum Dryer Jet Air System in Powdered Honey Process - Anang Lastriyanto; Khoiril Anam; La Choviya Hawa (Jurnal Ilmu Pertanian Indonesia, 2025)
Powdered honey represents a development from liquid honey to a powdered form. Product development is a critical component for businesses to be sustainable. Powdered honey processing is significant because it extends shelf life, facilitates transportation and storage, and makes it easier to utilize in a variety of food and beverage items. Furthermore, powdered honey can broaden market reach, provide value, and meet consumer desire for more practical and long-lasting products. Producers can use economic analysis to examine several components of their final product. By taking essential elements into account, business leaders can make better judgments about investments, machinery selection, and cost control to optimize earnings. The purpose of this study was to evaluate the economics of using vacuum drying equipment with a jet air system to produce powdered honey. The investigation was carried out at the Lastrindo Engineering Laboratory in Klojen, Malang, Indonesia. The results show that producing powdered honey with a vacuum drying machine and a jet air system has a positive NPV of IDR 640,134,063; a B/C Ratio of 1.22; and an IRR of 73.93%, making the investment plan for this machine economically viable. According to sensitivity analysis, increases in raw material prices and labor wages have a smaller impact than a loss in production, which has the greatest influence on the vacuum drying machine's profitability in powdered honey manufacturing. Keywords: economic analysis, powdered honey, vacuum dryer